1989
DOI: 10.1152/ajpheart.1989.256.3.h688
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory effects of DL-homocysteic acid in caudal ventrolateral medulla

Abstract: We carried out experiments in urethan-anesthetized rats to determine 1) whether increasing the activity of small groups of neurons in the caudal ventrolateral medulla (CVLM) by injecting picomoles of an excitatory amino acid altered cardiovascular and/or respiratory homeostasis and 2) whether the depressor responses after chemical excitation in the CVLM were elicited only from the immunohistochemically identified catecholamine-containing cell group. In discrete sites in the CVLM, unilateral injections of 1-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
6
23
1
Order By: Relevance
“…18 It has been shown that intracerebroventricular injection of Ang II produces an increase in norepinephrine turnover in the Al area, 19 which raises the possibility that the depressor effects of Ang II could be mediated by an increase in the activity of Al cells. On the other hand, a recent study in the rat 20 indicated that excitation of Al cells does not produce a depressor response. Thus, despite the evidence that there is an interaction between central Ang II and brain catecholamine systems, 19 -21 the depressor effect produced by Ang II in the caudal VLM may be due to an action on non-Al cells.…”
Section: Discussionmentioning
confidence: 90%
“…18 It has been shown that intracerebroventricular injection of Ang II produces an increase in norepinephrine turnover in the Al area, 19 which raises the possibility that the depressor effects of Ang II could be mediated by an increase in the activity of Al cells. On the other hand, a recent study in the rat 20 indicated that excitation of Al cells does not produce a depressor response. Thus, despite the evidence that there is an interaction between central Ang II and brain catecholamine systems, 19 -21 the depressor effect produced by Ang II in the caudal VLM may be due to an action on non-Al cells.…”
Section: Discussionmentioning
confidence: 90%
“…The vast majority of morphological and electrophysiological lines of evidence suggest that cVRG expiratory neurons probably are not involved in the respiratory rhythmogenesis since they do not have axon collaterals and therefore connections with other medullary respiratory neurons (Merrill 1979;Von Euler 1986;Huang and St John 1988;Bianchi et al, 1995;Iscoe 1998). However, activation of cVRG neurons through microinjections of EAA receptor agonists caused transient inhibition of inspiratory activity in cats (Bongianni et al, 1994), rats (Bonham and Jeske 1989;Chitravanshi and Sapru 1999) and rabbits (Bongianni et al, 2005). Actually, microinjections of the broad-spectrum EAA receptor agonist D,Lhomocysteic acid (DLH) into the cVRG of the cat provoked the activation of expiratory motoneurons and a corresponding silent period in phrenic nerve activity (Bongianni et al, 1994).…”
Section: Caudal Ventral Respiratory Group (Nucleus Retroambigualis)mentioning
confidence: 99%
“…Effect of CVLM microinjection of ANG- (1)(2)(3)(4)(5)(6)(7) and ANG II on baroreflex sensitivity. Unilateral microinjection of ANG-(1-7) into the CVLM produced a significant decrease in MAP (baseline MAP ϭ 110 Ϯ 6 mmHg, ⌬MAP ϭ Ϫ11 Ϯ 1.5 mmHg, n ϭ 10) that was similar to the decrease produced by ANG II (baseline MAP ϭ 99 Ϯ 5 mmHg, ⌬MAP ϭ Ϫ11 Ϯ 1.9 mmHg, n ϭ 13).…”
Section: Effect Of Rvlm Microinjection Of Ang-(1-7)mentioning
confidence: 99%
“…Peripheral mechanism involved in the baroreflex modulatory effects induced by microinjection of ANG- (1)(2)(3)(4)(5)(6)(7) or ANG II into the CVLM. We next evaluated the contribution of the parasympathetic tonus to the modulatory effect of the ANG peptides at the CVLM on the baroreflex control of HR.…”
Section: Effect Of Rvlm Microinjection Of Ang-(1-7)mentioning
confidence: 99%